KOMPARASI HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF STAD DAN MODEL TAI DI KELAS X IPS - Eka Yanti; Agus Sastrawan Noor; Agus Sugiarto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine the difference in the average scores of student learning results in Geography instruction between the group applying the Student Team Achievement Division learning model and the group applying the Team Assisted Individualization learning model in class X SMA N 9 Pontianak. The research method used was experimental in the form of a quasi-experimental design with a nonequivalent control group design. The sampling technique used was purposive sampling. Based on the calculation, the average final test result of experimental group I was 60.550, while the result of experimental group II was 65,256. The results of hypothesis testing using the T-test obtained the tcount of 4.637. Based on the distribution list of t-table values for the two-sided test with α = 0.05, obtained ttable = 2.038, meaning that tcount > ttable (4.637> 2.038) and thus Ha is accepted. Therefore, there was a significant difference in the average student learning outcomes in geography learning between the group applying the Student Team Achievement Division model and the group applying the Team Assisted Individualization learning model in class X SMA N 9 Pontianak.Keywords: Learning Outcomes, Student Team Achievement Division, Team Assisted Individualization.